Chinese herbal remedies affecting thrombosis and hemostasis: A review - Quan Li (World Journal of Traditional Chinese Medicine, 2015)
Acute coronary syndrome, stroke and other ischemic events continue to be the most common causes of mortality and morbidity in the world, and their incidence is rapidly increasing in the developing nations. These cardiovascular disorders clinically manifest as acute atherothrombotic events. Application of oral antiplatelet drugs is a milestone in the therapy of cardiovascular diseases. However, the limited efficacy of these drugs in the setting of arterial thrombosis, their unfavorable side effects, cost-to-benefit issues and the drug resistance phenomenon substantiate the need for the development of new and more efficacious antithrombotic drugs. In recent years, with the progress in the study of the Chinese medicine pharmacology, many Chinese herbs and formulas, as well as active constituents have been reported to possess not only effects on platelet aggregation and activation but also beneficial roles in vascular functions. Compared with currently used antithrombotic agents, herb remedies exert antithrombotic effects in a multi-pathway and multi-target manner. This paper will cover the progress in research on the ameliorating effects of herbal remedies on thrombosis, with focusing on their protection of vascular endothelial cells and inhibition of platelet activation.